Emerging roles of vasoactive intestinal peptide: a new approach for autoimmune therapy. (12th October 2007) - Gonzalez-Rey, Elena; Anderson, Per; Delgado, Mario
Abstract : Identification of the factors that regulate the immune tolerance and control the appearance of exacerbated inflammatory conditions is crucial for the development of new therapies of autoimmune diseases. Some neuropeptides and hormones have emerged as endogenous agents that participate in the regulation of the processes that ensure self-tolerance. Among them, the vasoactive intestinal peptide (VIP), a well-characterised endogenous anti-inflammatory neuropeptide, has shown therapeutic potential for a variety of immune disorders. Here we examine the latest research findings, which indicate that VIP participates in maintaining immune tolerance in two distinct ways: by regulating the balance between pro-inflammatory and anti-inflammatory factors, and by inducing the emergence of regulatory T cells with suppressive activity against autoreactive T cell effectors.